2022
DOI: 10.3390/molecules27020422
|View full text |Cite
|
Sign up to set email alerts
|

Growth Performance, Biochemical Composition and Nutrient Recovery Ability of Twelve Microalgae Consortia Isolated from Various Local Organic Wastes Grown on Nano-Filtered Pig Slurry

Abstract: This paper demonstrated the growth ability of twelve algae-microbial consortia (AC) isolated from organic wastes when a pig slurry-derived wastewater (NFP) was used as growth substrate in autotrophic cultivation. Nutrient recovery, biochemical composition, fatty acid and amino acid profiles of algae consortia were evaluated and compared. Three algae-microbial consortia, i.e., a Chlorella-dominated consortium (AC_1), a Tetradesmus and Synechocystis co-dominated consortium (AC_10), and a Chlorella and Tetradesmu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 78 publications
4
15
0
Order By: Relevance
“…The most abundant amino acids in all microalgae species were Arg, Asp, Ala, Lys, and Glu, followed by Pro, Leu, Gly, and Ser. These results agree with previous studies [ 51 , 52 , 53 ], even if other authors reported higher amino acid amounts, comparable to those of eggs and soybeans [ 54 , 55 ]. These differences in values can be due to different harvesting regimes and seasons, drying processes, and strains [ 56 , 57 ].…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…The most abundant amino acids in all microalgae species were Arg, Asp, Ala, Lys, and Glu, followed by Pro, Leu, Gly, and Ser. These results agree with previous studies [ 51 , 52 , 53 ], even if other authors reported higher amino acid amounts, comparable to those of eggs and soybeans [ 54 , 55 ]. These differences in values can be due to different harvesting regimes and seasons, drying processes, and strains [ 56 , 57 ].…”
Section: Resultssupporting
confidence: 93%
“…Knowledge of amino acid (AA) composition (with particular reference to essential amino acids, EAAs) of microalgae has great importance in the establishment of their nutritional value and potential uses in food applications [ 51 ]. According to the different total protein content, the amino acid content of the ingredients from the four microalgae species included in this study ( Table 1 ) differed significantly, except for cysteine.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, the pH of raw wastewater and sterilized wastewater was maintained between 7.00-7.75 and 6.96-7.67, respectively. Therefore, the volatilization of NH + 4 -N and phosphate precipitation at pH > 9 were not involved [38], indicating that the pollutant removal by T. cf. obliquus ZYY1 was mainly through assimilation.…”
Section: Wastewatermentioning
confidence: 99%
“…In it, twelve algae consortia (ACs) were isolated from sixteen different organic wastes [17]. Then the ACs were tested to treat organic wastes, removing nutrients and producing useful biomass in different modes, i.e., autotrophic mode, as previously reported [12], and mixotrophic mode (this paper), at batch scale, before up-scaling to a pilot plant.…”
Section: Introductionmentioning
confidence: 99%
“…Microalgae-based processes can reduce by up to half the energy consumption of conventional wastewater treatment and allow the recovery of up to 90% of the nutrients contained in wastewater [11]. Nano-filtered pig slurry permeate (NFP) is the effluent of a pig slurry treatment factory, which contains a high percentage of ammonium (NH 3 -N) in low concentrations and could be considered a suitable nitrogen source to support algal growth [12] since algae prefer ammonium N as the N source.…”
Section: Introductionmentioning
confidence: 99%